Composite Transport Model and Water and Solute Transport across Plant Roots: An Update - Kim, Yangmin X.; Ranathunge, Kosala; Lee, Seulbi; Lee, Yejin; Lee, Deogbae; Sung, Jwakyung (Frontiers in Plant Science, 2018)
The present review examines recent experimental findings in root transport phenomena in terms of the composite transport model. It has been a well-accepted conceptual model to explain the complex water and solute flows across the root that has been related to the composite anatomical structure. There are three parallel pathways involve in the transport of water and solutes in roots – apoplast, symplast and transcellular paths. The role of aquaporins, which facilitate water flows through the transcellular path, and root apoplast were examined in terms of the composite transport model. The contribution of the plasma membrane bound aquaporins for the overall water transport in the whole plant level was varying depending on the plant species, age of roots with varying developmental stages of apoplastic barriers, and driving forces (hydrostatic vs. osmotic). Many studies have demonstrated that the apoplastic barriers, such as Casparian bands in the primary anticlinal walls and suberin lamellae in the secondary cell walls, in the endo- and exodermis are not perfect barriers and unable to completely block the transport of water and some solute transport into the stele. Recent research on water and solute transport of roots with and without exodermis triggered the importance of the extension of conventional composite transport model adding resistances that arrange in series (epidermis, exodermis, mid cortex, endodermis, and pericycle). The extension of the model may answer current questions about the applicability of composite transport model for composite water and solute transport of roots that contain complex anatomical structures with heterogeneous cell layers.